2019
DOI: 10.1016/j.biortech.2019.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Process development for the production of prebiotic fructo-oligosaccharides by penicillium citreonigrum

Abstract: A new isolated P. citreonigrum URM was selected to produce fructooligosaccharides (FOS) in an efficient, economical and fast one-step fermentation. Optimal culture conditions were stablished by experimental design. Experiments run in bioreactor resulted in a high yield, content, productivity and purity of FOS (0.65 ± 0.06 g FOS /g initial Sucrose , 126.3 ± 0.1 g/L, 2.28 ± 0.08 g/L.h and 61 ± 0%). The FOS mixture was purified up to 92% (w/w) with an activated charcoal column. FOS produced were able to promote l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 48 publications
1
16
1
Order By: Relevance
“…Compared with the results reported by Muñiz-Márquez et al [10] for Aspergillus oryzae DIA-MF fermentation using aguamiel as the substrate by a one-stage process in batch culture, FOS concentration, yield, and productivity were 26.0 times, 130.0%, and 9.9 times higher, respectively. Compared with the results reported by Nobre et al [13] for Penicillium citreonigrum using a one-stage process in batch culture, the FOS concentration, yield, and productivity were 3.3 times, 6.1%, and 3.0 times higher, respectively. Compared with the results reported by Schorsch et al [18] for Aspergillus sp.…”
Section: Fos Production In a Membrane Integrated Repeated Batch Culturecontrasting
confidence: 74%
See 2 more Smart Citations
“…Compared with the results reported by Muñiz-Márquez et al [10] for Aspergillus oryzae DIA-MF fermentation using aguamiel as the substrate by a one-stage process in batch culture, FOS concentration, yield, and productivity were 26.0 times, 130.0%, and 9.9 times higher, respectively. Compared with the results reported by Nobre et al [13] for Penicillium citreonigrum using a one-stage process in batch culture, the FOS concentration, yield, and productivity were 3.3 times, 6.1%, and 3.0 times higher, respectively. Compared with the results reported by Schorsch et al [18] for Aspergillus sp.…”
Section: Fos Production In a Membrane Integrated Repeated Batch Culturecontrasting
confidence: 74%
“…[10,11], Bacillus subtilis [12] and Penicillium spp. [13]. The FOS are then produced under controlled conditions with the extracted enzymes using sucrose as the substrate [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Profeed (Tereos, France) and Nutra ora P-95 (Ingredion, Canada) have similar GF 3 /GF 2 ratios of 1.43:1 but different GF 4 /GF 2 ratios (0.27:1 for Profeed vs 0.36:1 for Nutra ora) according to their product speci cations. In contrast, Actilight (Tereos, France) and one FOS product from GCT Nutrition (Nobre et al) had a similar high level of GF 3 /GF 2 ratio of ~ 1.7:1 but different GF 4 /GF 2 ratios (0.20:1 for Actilight and 0.30:1 for GCT FOS) (Kaplan and Hutkins 2000;Nobre et al 2019). Studies also showed probiotics such as Lactobacillus and Bi dobacterium strains had different responses towards FOS products such as NutraFlora P-95, Raftilose P95 and Inulin-S from different companies and/or sources (Huebner et al 2007).…”
Section: Effect Of Exogenous Nano 3 and Na 2 Hpomentioning
confidence: 99%
“…For the production of FOS, a high concentration of initial sucrose is required (Hidaka, Hirayama, & Sumi, 1988;Dominguez, Rodrigues, Lima, & Teixeira, 2013). Several strains have been reported as producers of these FOS producing enzymes, between them fungi are the most reported strains: Aspergillus japonicus (Mussatto, Aguilar, Rodrigues, & Teixeira, 2009Mussatto & Teixeira, 2010;Sheu, Chang, Wang, Wu, & Huang, 2013), Aspergillus ibericus (Nobre et al, 2018a;2018b), Aspergillus oryzae (Muñiz-Márquez et al, 2019, Aspergillus niger (Lateef, Oloke, Gueguim-Kana, & Raimi, 2012), Aureobasidium pullulans (Castro, Nobre, Duprez, De Weireld, & Hantson, 2017, 2019Dominguez et al, 2012;Lateef, Oloke, & Prapulla, 2007), Rhizopus stolonifer (Lateef et al, 2008; and Penicillium citreonigrum (Nobre et al, 2019;Nascimento, Nobre, Cavalcanti, Teixeira, & Porto, 2016). At industrial level, when enzymes are produced, components of the growth media represent around 30-40% of the production cost, mainly contributed by carbon and nitrogen sources (Laxman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%